Caracterización del sector metalmecánico de Cúcuta - Sandra Milena Rozo Rincón; Claudia Liliana Casadiego Peralta; Camila Andrea Valencia Rodríguez (Mundo Fesc)
Considering the lack of knowledge regarding various aspects of the Cúcuta metalworking sector, a study was conducted to identify the structure of the metalworking sector in the municipality of Cúcuta, related to metal processing, taking into account productive, technological, and human talent aspects. The consolidated information is based on an analysis of a representative group of companies in the sector registered with the Cúcuta Chamber of Commerce with renewal valid until 2019, using a survey as a data collection instrument. The results show that the Cúcuta metalworking sector is characterized by a high level of informality and low product diversification given the companies' focus on providing services related to ferrous metal processing. In addition to its incipient technology, it is also characterized by a low level of contracting, highlighting the sector's strong dependence on Venezuela in recent years. The results are a source of information for future projects related to the search for alternatives to strengthen this sector, which, in the national case, generates significant contributions to the Colombian economy.